(untitled) (The Pakistan Development Review, 1996)
The informal credit market is of crucial importance in the rural areas in Pakistan, even after decades of considerable development of formal credit organisations and of subsidised credit programmes by the government. This is due mainly to the fact that informal credit relations are embedded in the economic, political, and social interaction networks of the inhabitants in the rural areas. These interaction networks also maintain the direct credit costs and the transaction costs at a low level. However, the national development policy underestimates or even negates the significance of the informal financial market. Here, political action is required for initiating change.